Extended X-Ray Absorption Fine Structure of ZrW2O8: Theory vs. Experiment - Vila, Fernando D.; Spencer, John W.; Kas, Joshua J.; Rehr, John J.; Bridges, Frank (Frontiers in Chemistry, 2018)
Extended x-ray absorption fine structure (EXAFS) is well suited for investigations of structure and disorder of complex materials. Recently, experimental measurements and analysis of EXAFS have been carried out to elucidate the mechanisms responsible for the negative thermal expansion (NTE) in zirconium tungstate (ZrW2O8). In contrast to previous work suggesting that transverse O-displacements are largely responsible, the EXAFS analysis suggested that correlated rotations and translations of octahedra and tetrahedra within the structure are a major source. In an effort to resolve this controversy, we have carried out ab initio calculations of the structure, lattice vibrations, and EXAFS of ZrW2O8 based on real-space multiple-scattering calculations using the FEFF9 code and auxiliary calculations of structure and Debye-Waller factors. We find that the theoretical simulations are consistent with observed EXAFS, and show that both of the above mechanisms contribute to the dynamical structure of ZrW2O8.